Association of castor bean oil with Beauveria bassiana for diamondback moth control - Rondelli, Vando Miossi; Pratissoli, Dirceu; Polanczyk, Ricardo Antonio; Marques, Edmilson Jacinto; Sturm, Gustavo Martins; Tiburcio, Marcel Oliveira (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the efficiency, the stability, the application mode and the compatibility between castor bean oil and the entomopathogenic fungus Beauveria bassiana, for diamondback moth (Plutella xylostella) control. In the first experiment, the efficiency, the stability after 70 days of storage, and the application mode of castor bean oil were evaluated. In the second one, the compatibility of castor bean oil with B. bassiana was evaluated. The insecticidal activity of the castor bean oil is unstable over time. The castor bean oil is compatible with B. bassiana against P. xylostella.